Knowledge Map : Equity Issues - Gender, Special Needs and Marginalized Groups - World Bank (Washington, DC, 2012)
Equity issues are critical and acute. It is clear that there are critical equity issues related to the uses of information and communication technologies (ICTs) in education. There is a real danger that uses of ICTs can further marginalize groups already excluded or marginalized from existing educational practices and environments. Solid documentation from Organization for Economic Co-operation and Development (OECD) countries. There is a richly documented history of what works and what doesn't related to the uses of ICTs to assist in the education of students with a variety of disabilities, both cognitive and physical based on OECD experience. Certain applications of ICTs have been shown to have positive and important effects on the educational development of students exhibiting a great variety of special needs (including blind, deaf, and learning disabled students). While ample evidence exists that ICT use can have a positive impact on student motivation, such gains in motivation tend to correlate most closely with students who are already the most academically motivated and highest achievers.